Philosophy and literature from perspective of Bloom, Kundera, Borges and Rorty - Silva, Heraldo Aparecido (Sofia, 2023)
The purpose of this paper is to present some considerations on the relationship between philosophy and literature. For comparative purposes, the notion of wisdom literature by literary critic Harold Bloom is used as central element for articulation with the conception of novelist and essayist Milan Kundera and the neopragmatist philosopher Richard Rorty. The contrast between the positions of Bloom, Kundera and Rorty has divergent lines of argument on some point of the philosophical-literary relationship. However, inadvertently, the authors converge on the practical purpose of some aspects of philosophy and literature, with regard to the context of their respective investigations on fundamental themes to the understanding of human existence.
Keywords: literature; philosophy; novel; wisdom literature; philosophical literature